Assessment of transient dopamine responses to smoked cannabis. (1st October 2021) - Calakos, Katina C.; Liu, Heather; Lu, Yihuan; Anderson, Jon Mikael; Matuskey, David; Nabulsi, Nabeel; Ye, Yunpeng; Skosnik, Patrick D.; D'Souza, Deepak Cyril; Morris, Evan D.; Cosgrove, Kelly P.; Hillmer, Ansel T.
Highlights: Dopamine mechanisms of cannabis' reinforcing effects are not well studied in people. Positron Emission Tomography imaging of dopamine D2/D3 receptors was performed. Participants smoked a cannabis cigarette while in the scanner. Dopamine responses were detected by modeling short-lived reductions in receptor binding. The majority of detected clusters were located in ventral striatum. Abstract: Background: Dopaminergic mechanisms that may underlie cannabis' reinforcing effects are not well elucidated in humans. This positron emission tomography (PET) imaging study used the dopamine D2/3 receptor antagonist [ 11 C]raclopride and kinetic modelling testing for transient changes in radiotracer uptake to assess the striatal dopamine response to smoked cannabis in a preliminary sample. Methods: PET emission data were acquired from regular cannabis users ( n = 14; 7 M/7 F; 19–32 years old) over 90 min immediately after [ 11 C]raclopride administration (584 ± 95 MBq) as bolus followed by constant infusion ( K bol = 105 min). Participants smoked a cannabis cigarette, using a paced puff protocol, 35 min after scan start. Plasma concentrations of Δ 9 -THC and metabolites and ratings of subjective "high" were collected during imaging. Striatal dopamine responses were assessed voxelwise with a kinetic model testing for transient reductions in [ 11 C]raclopride binding, linear-parametric neurotransmitter PET (lp-ntPET) (cerebellum as a reference region). Results: Cannabis smoking increased plasma Δ 9 -THC levels (peak: 0−10 min) and subjective high (peak: 0−30 min). Significant clusters (>16 voxels) modeled by transient reductions in [ 11 C]raclopride binding were identified for all 12 analyzed scans. In total, 26 clusters of significant responses to cannabis were detected, of which 16 were located in the ventral striatum, including at least one ventral striatum cluster in 11 of the 12 analyzed scans. Conclusions: These preliminary data support the sensitivity of [ 11 C]raclopride PET with analysis of transient changes in radiotracer uptake to detect cannabis smoking-induced dopamine responses. This approach shows future promise to further elucidate roles of mesolimbic dopaminergic signaling in chronic cannabis use. ClinicalTrials.gov Identifier: NCT02817698.